Sub-nanosecond Optical Switching Using Chip-Based Soliton Microcombs - Lange, Sophie; Raja, A.S.; Shi, Kai; Karpov, M.; Behrendt, Raphael; Cletheroe, Daniel; Haller, Istvan; Karinou, Fotini; Fu, X.; Liu, J.; Lukashchuk, A. .; Thomsen, Benn; et al. (Optical Fiber Communication Conference (OFC), 2020)
We demonstrate sub-nanosecond wavelength switching of a soliton microcomb laser, using a semiconductor optical amplifier-based wavelength selector. We demonstrate the proof-of-concept transmitting 50Gbps PAM4 and 25Gbps NRZ with an integrated wavelength selector.